Teachers’ Beliefs and Implementation in Mathematics Learning - Ahmad Abdul Mutholib; Imam Sujadi; Sri Subanti (Pancaran Pendidikan, 2017)
The objectives of the research are (1) to identify teachers’ beliefs in teaching, (2) to identify the factors that influence their belief and practice in teaching, and (3) to identify the implementation of teachers’ beliefs in teaching. The subjects of the research are two mathematics teachers. The data are collected through observation, interview, and document analysis. Interactive models from Miles and Huberman were used to examine the data. The findings of this research are: (1) there are some similarities and differences between teachers’ beliefs in a teaching of accountancy and tourism teachers. The similarities and differences are in education and teaching and in curricula. Meanwhile, in teaching profession, the teachers have same beliefs, (2) there are seven factors which affect teachers’ beliefs and practice in teaching that consist of teaching experience, learning experience, classroom management, student’s family, students’ colleagues, motivation, and teaching media, and (3) dealing with teaching practice, accountancy teacher does continuous teaching in which one genre is taught continuously to the next meeting, while tourism teacher does one finished teaching in which one genre is taught in one meeting. In their teaching practice, there are some beliefs about education and teaching and about curricula are not implemented, while beliefs about teaching profession are implemented. The inconsistency between teachers’ beliefs and teaching practices is caused by affecting factors revealed by the teachers. Therefore, it is important for teachers to reduce the factors that impede the smoothness of teachers’ beliefs in teaching practice or even change their teaching belief if it cannot facilitate students to learn.